Aptian to turonian radiolarians from chert blocks in the Kuamut Melange, Sabah, Malaysia - Basir Jasin; Junaidi Asis (Universiti Kebangsaan Malaysia, 2013)
The Kuamut Melange is located in the Kunak district, southeast Sabah. The mélange consists of clasts and blocks of broken Paleogene formations, and dismembered ophiolite blocks embedded in shale matrix. Fourteen samples were collected from sections S1 and S2 of the Kuamut Melange. A total of 45 species of radiolarians have been identified and only 36 selected species are used for age determination. Three assemblages (I-III) were identified. Assemblage I consists of Dictyomitra excellence, Crucella bossoensis, Hiscocapsa asseni, Hexapyramis precedis, Thanarla brouweri, Acanthocircus levis, Obeliscoites vinassai, Stichomitra communis, Staurosphaeretta longispina, Xitus spicularius, Triactoma cellulosa, and Dactyliosphaera maxima. This assemblage is marked by the occurrence of Crucella gavalai indicative of Aptian to Albian in age. Assemblage II was characterized by zonal maker Xitus mclaughlini. Other species in this assemblage are Xitus spinosus, Stichomitra tosaensis, Dictyomitra gracilis, Dictyomitra montisserei, Pseudodictyomitra pseudomacrocephala, Pessagnobrachia fabianii, Crucella messinae, Tuguriella pagoda, Dictyomitra obesa, Triactoma paronai, Rhopalosyringium euganeum, Acanthocircus venetus, Acaeniotyle rebelis, Dictyomitra formosa, Pseudodictyomitra tiara and Patellula helios. This assemblage ranges from Albian to Cenomanian. Assemblages III is represented by zonal maker Crucella cachensis and others species in this assemblage are Hemicryptocapsa polyhedra, Eostichomitra bonum, Pseudotheocampe tina, Ultranapora cretacea and Alievium superbum. Assemblage III is Turonian in age. The radiolarian assemblages suggest that the age of chert blocks ranges from Aptian to Turonian, Cretaceous. The cherts were originally deposited on an oceanic crust of a marginal basin during Cretaceous and were tectonically deformed to form melange in Miocene time.